Green synthesis, Optimization and Characterization of SiO2 nanoparticles using Aspergillus tubingensis F20 isolated from drinking water - Sohila A. Abd Elmohsen; Samah A. Mohmed; Ghadir E. Daigham; Essam M. Hoballah; Nagwa M. Sidkey (Novel Research in Microbiology Journal, 2019)
This study aimed to demonstrates a positive correlation between silica metal tolerance ability of a drinking water fungi and its potential for the synthesis of silica oxide (SiO2) nanoparticles (NPs). Metal oxide NPs can be synthesized biologically by different methods including; microorganisms, plant extracts and\ or plant biomass. These methods in some time are better alternatives to the chemical and physical methods through an environmentally route. In the present work, twenty fungal strains were isolated from eight potable water samples and tested for producing silica nanoparticles (SiO2NPs), using precursor salt Dipotassium fluorosilicate (K2SiF6). Out of these twenty fungal strains, only one fungal isolate had the potency to reduce metal salt into metal NPs, which was identified by a molecular assay as Aspergillus tubingensis F20, and was assigned an Accession number of (MK226258.1) using the NCBI GenBank database. The factors affecting mono-dispersed production of SiO2 NPs such as; reaction times, incubation temperatures, hydrogen ion concentrations (pH) and salt concentrations were optimized. It is revealed that 10-3 M precursor salt concentration, 72 h of reaction time at pH 3, and an incubation temperature 28°C are the optimum conditions for the production of smaller size NPs. The biosynthesized NPs was characterized using several techniques including; Dynamic light scattering (DLS), Transmission Electron Microscopy (TEM), Scanning Electron Microscopy (SEM), and Energy dispersive X-ray spectroscopy (EDX). It is observed that the shape of SiO2NPs is spherical with an average size of 8 nm, and surface charge of - 8.19 mv, which indicates that SiO2NPs is more stable.